Practical tips on vaccination in multiple sclerosis patients - Dagmara Mirowska-Guzel; Aneta Nitsch-Osuch (Family Medicine & Primary Care Review, 2023)
Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system of unclear aetiology which involves genetic and envi-ronmental factors, including infections. Infections in MS patients increase the risk of exacerbation of the disease. It has been shown that preventing infections reduces the risk of MS relapse and quality of life outcome. Over the past 20 years, the number of drugs available for disease modifying therapy (DMT) in MS patients has grown significantly. Some of the DMT may entail an increased risk of infections, including life-threatening ones such as measles... etc. These infections include measles, infections caused by human papilloma virus (HPV), varicella zoster virus (VZV), hepatitis B virus (HBV), pneumococci and, recently, serious acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Therefore, at the time of MS diagnosis, the patient should be interviewed and screened for prior vaccination and/or serological status prior to starting DMT so that any missing vaccinations can be performed. Most infections can be effectively and safely prevented. Vaccinations should be integral part of the treatment process. They not only prevent life-threatening diseases but also increase the safety of drugs used to change the course of the underlying disease. Some specific recommenadation regarding the use of vaccinations in MS patients treated with DMT are included in summary of product characteristic for particular drugs. Additionally, scientific boards publish guidelines on recommended vaccinations due to changing epidemiological situations with special emphasis on immunocompromised patients.